2021
DOI: 10.1101/2021.03.03.433712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sugar transporters enable a leaf beetle to accumulate plant defense compounds

Abstract: Many herbivorous insects selectively accumulate plant toxins for defense against predators; however, little is known about the transport processes that enable insects to absorb and store defense compounds in the body. Here, we investigate how a specialist herbivore, the horseradish flea beetle, accumulates high amounts of glucosinolate defense compounds in the hemolymph. Using phylogenetic analyses of coleopteran membrane transporters of the major facilitator superfamily, we identified a clade of glucosinolate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We recently identified glucosinolatespecific transporters belonging to the major facilitator superfamily (MFS) in P. armoraciae and found two glucosinolate transporters to be expressed in the foregut, suggesting a role in glucosinolate uptake. However, silencing the expression of these transporters did not affect the uptake of ingested glucosinolates in adults, which indicates that additional or other transporters mediate glucosinolate absorption in P. armoraciae (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…We recently identified glucosinolatespecific transporters belonging to the major facilitator superfamily (MFS) in P. armoraciae and found two glucosinolate transporters to be expressed in the foregut, suggesting a role in glucosinolate uptake. However, silencing the expression of these transporters did not affect the uptake of ingested glucosinolates in adults, which indicates that additional or other transporters mediate glucosinolate absorption in P. armoraciae (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…(2010) found that generalist herbivores were negatively affected by both indole and aliphatic GSL, whereas specialist herbivores were not affected. Many specialist herbivores of brassicaceous plants have evolved mechanisms to detoxify or sequester GSLs (Textor & Gershenzon, 2009; Jeschke et al ., 2016; Yang et al ., 2021). Delia radicum harbours gut microbes that can detoxify breakdown products of the aromatic GSL gluconasturtiin (Welte et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Using mutant Arabidopsis plants, Müller et al (2010) found that generalist herbivores were negatively affected by both indole and aliphatic GSL, but specialist herbivores were not affected. Many specialist herbivores of brassicaceous plants have evolved mechanisms to cope with GSLs (Textor & Gershenzon, 2009;Jeschke et al, 2016), and some species are even capable of sequestering specific GSLs for their own defence (Yang et al, 2021). Delia radicum harbours gut microbes that can detoxify breakdown products of the aromatic GSL gluconasturtiin (Welte et al, 2016).…”
Section: Discussionmentioning
confidence: 99%